PENGARUH MODEL INKUIRI TERBIMBING DIPADU KOOPERATIF JIGSAW TERHADAP KETERAMPILAN PROSES SAINS DITINJAU DARI KEMAMPUAN AKADEMIK - Rokhmatika, Siti; Harlita, Harlita; Prayitno, Baskoro Adi (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The purposes of this research are to ascertain: 1) the influence of Guided Inquiry combined Cooperative Jigsaw model toward science process skills, 2) the influence of academic ability toward science process skills, 3) the interaction between Guided Inquiry combined Cooperative Jigsaw model and academic ability toward science process skills. The research was quasi experiment research. The research was designed using pretest posttest nonequivalent control group design. Experimental group applied Guided Inquiry combined Cooperative Jigsaw model. Control group applied Conventional model. The populations of this research were all of 10th degree students at SMA Negeri 2 Surakarta in academic year 2011/2012. The samples of this research were the students of X-1 as experiment group and X-3 as control group. The sample of this research was established by cluster random sampling. The data was collected essay test, observation form, and document. The hypotheses analyzed by Anacova. The research concluded that 1) application of Guided Inquiry combined Cooperative Jigsaw model had significant effect toward science process skill, 2) the academic ability didn?t has significant effect toward science process skill, 3) there was not interaction between Guided Inquiry combined Cooperative Jigsaw model and academic ability toward science process skills. Keywords: Guided Inquiry, Cooperative Jigsaw, Academic Ability, Science Process Skills .